Polski teatr na emigracji - Braun, Kazimierz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
A great number of individual Polish actors and small theatre companies are active all over the world; sometimes, a visiting production from Poland excites the émigré audiences strengthening their ties with the mother country. Two key notions help to understand both the ethos and the history of theatre of Polish émigrés: (1) “Citizen’s theatre” is a theatre in which spiritual, human, ethical, patriotic and communal values play the most important role, while aesthetic and utilitarian values are secondary. (2) “Theatre of service”, which is created in order to serve the spectators, to help them to preserve their traditions, support their needs, and express their hopes. The structure of theatre life of Polish émigrés can be visualized as a three-layer pyramid. Its foundation is made of dense and ubiquitous “theatricality of life”, which permeates all areas of life, such as social, familial, religious, political, academic, sport, or commerce. Manifestations of “theatricality” include weddings, anniversaries, parades, jubilees, funerals, liturgies, processions, celebrations of Christmas, Easter, or Corpus Christi, and other events and activities. They use Polish imagery, symbols, costumes and/or songs. “Theatricality” employs theatre’s categories: action, characters, structuring the space and the time of the event, as well as theatre’s means of expression. Above “theatricality” is a deep layer of amateur theatre practiced at schools, parishes and various associations and organizations. Polish amateur productions in the US have been recorded since the 1870s in the cities of especially numerous Polish population such as Chicago, Buffalo, Detroit, Pittsburgh, Philadelphia and New York. Polish amateur theatre companies can be found in many countries. The tip of the pyramid consists of the performances given by Polish professionals abroad and tours of Polish productions. Helena Modrzejewska, in America known as Modjeska (1840-1909), after stardom in Kraków and Warsaw arrived in America in 1876, and made a splendid, thirty years lasting career on American stages, performing in English. In the 1880s she was considered the greatest American female stage star. Ryszard Bolesławski (1889-1937) in his youth was an actor and director at Moscow Art Theatre of K. Stanislavsky. When Poland regained its independence (1918), he returned to Warsaw and directed at the Polski Theatre. In 1922, he went to America where he directed and taught acting, first in New York’s theatres and acting studios, and then in the film industry in Hollywood. He is credited for introducing American actors to the realisticpsychological Stanislavsky’s method, with a poetic, typically Polish tint. Polish professional theatre companies were active outside of Poland during World War II in New York (1942–1945) and in London (1942-until present). In 1943, professional theatres were organized at the Polish Armed Forces by Jadwiga Domańska, and at the Polish Division under the Soviet command by Władysław Krasnowiecki. Polish professional productions were also created in Rumania, France, Brazil, British Palestine and elsewhere. After the war, the strongest Polish theatre centre east of Poland (in its borders established at the Jalta conference, 1945) was Teatr Polski established in Lwów in 1958, by actor and director Zbigniew Chrzanowski, while at the West, it was the Polski Instytut Teatralny in New York managed since 1976, by actress and director Janina Katebach (Nina Polan). In the 1970s and the 1980s Polish theatre life flourished in Ottawa, thanks to the works of Jadwiga Domańska; and since the 1990s, in Toronto, where actress and director Maria Nowotarska created permanent Polish stage, collaborating with a cluster of actors. Experimental theatres of Tadeusz Kantor, Jerzy Grotowski, and Włodzimierz Staniewski performed for international audiences. Great Polish actors, such as Elżbieta Czyżewska, Ryszard Cieślak, and Andrzej Seweryn, appeared in foreign productions. Plays written by best Polish playwrights – Stanisław Ignacy Witkiewicz, Witold Gombrowicz, Tadeusz Różewicz, Sławomir Mrożek – were staged in many countries. Books on Polish theatre and drama were published in several languages. Polish theatre scholars and artists lectured and taught at foreign universities. Polish productions created either within the émigré communities or visiting from Poland contributed to preservation of Polish language, traditions, and values. Generally, Polish theatre was a vibrant element of Polish culture abroad.
Theatre of polish émigrés
Keywords: emigracja XX w.; historia teatru